ICASSP 2020 - 2020 IEEE International Conference on Acoustics, Speech and Signal Processing (ICASSP) 2020
DOI: 10.1109/icassp40776.2020.9053216
|View full text |Cite
|
Sign up to set email alerts
|

Adversarial Networks for Secure Wireless Communications

Abstract: We propose a data-driven secure wireless communication scheme, in which the goal is to transmit a signal to a legitimate receiver with minimal distortion, while keeping some information about the signal private from an eavesdropping adversary. When the data distribution is known, the optimal trade-off between the reconstruction quality at the legitimate receiver and the leakage to the adversary can be characterised in the information theoretic asymptotic limit. In this paper, we assume that we do not know the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Hence, the RoI packets will require stringent security and reliability specifications, while the BG packets do not provide useful data if being revealed to the passive Eves. Remarkably, a content-based secure wireless image delivery is not addressed in many recently-published works in the area of wireless image transmission, e.g., [10], [20], [21]. In other words, they all consider a unified end-to-end approach for sending an image over the air, regardless of paying attention to the content/region of the image being transmitted at each transmission slot (TS).…”
Section: Contributionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, the RoI packets will require stringent security and reliability specifications, while the BG packets do not provide useful data if being revealed to the passive Eves. Remarkably, a content-based secure wireless image delivery is not addressed in many recently-published works in the area of wireless image transmission, e.g., [10], [20], [21]. In other words, they all consider a unified end-to-end approach for sending an image over the air, regardless of paying attention to the content/region of the image being transmitted at each transmission slot (TS).…”
Section: Contributionsmentioning
confidence: 99%
“…In this paper, different from the previous works of [7], [12]- [14], and [21], we take the delay limits of a practical image transmission system into account via utilizing a hybrid multi-packet transmission design. We then derive an exact closed-form expression, which was not obtained in [15]- [17], for the quality-of-security (QoSec) violating probability (QVP) as our performance metric to addresses the effect of delay limits on the image delivery.…”
Section: Contributionsmentioning
confidence: 99%
“…Similar data-driven wiretap channel approaches have recently been proposed for Gaussian channels in [16][17][18][19]. However, [16,18,19] focus on channel coding, and [18,19] enforce coding structure to the encoder, while we carry out endto-end joint learning corresponding to a JSCC approach.…”
Section: Introductionmentioning
confidence: 99%
“…The similarity between the communication systems and end-to-end learning motivates the use of autoencoder based neural network architectures, which simultaneously learn encoding and decoding [14,15]. Recently, it has been shown that end-to-end approaches can also be utilized for physical layer secrecy [16][17][18][19]. In a wiretap channel setting, these techniques exploit the physical characteristics of the legitimate receiver's channel over the eavesdropper's, and allow communication with secrecy guarantees.…”
Section: Introductionmentioning
confidence: 99%
“…In the context of wireless communication, one can approximate the channel distribution by samples and use the generator as a piece within the NN encoderdecoder chain [9], [10]. This was recently utilized to enable a form of secure communication in [11]. ii) Mutual information estimators: A recent breakthrough has shown that mutual information can be approximated through sampling of the random variables with the help of NNs [12].…”
Section: Introductionmentioning
confidence: 99%